Managing Organizational Ethics in the Public Sector: A Pluralist Contingency Approach as an Alternative to the Integrity Management Framework. (3rd July 2017) - Tremblay, Maryse; Martineau, Joé T.; Pauchant, Thierry C.
Abstract : Integrity management is the most widely advocated approach in the management of organizational ethics within the public sector. It calls for a balance between compliance and value approaches in order to implement appropriate controls, methods, instruments, and procedures that foster ethical behavior among organizational members. However, organizations do not yet have access to a tool or method that would allow them to measure this balance. By highlighting the main limitations of the integrity management framework, this article argues that such a tool has not yet been developed because it is extremely difficult to establish a balance between these two approaches. As its main contribution, the article proposes the adoption of a new pluralistic contingency approach in the management of organizational ethics, an approach that overcomes the limitations of the integrity management framework.